2006
DOI: 10.1002/jemt.20381
|View full text |Cite
|
Sign up to set email alerts
|

Collagen types I, III, and V constitute the thick collagen fibrils of the mouse decidua

Abstract: A mammal's endometrium is deeply remodeled while receiving and implanting an embryo. In addition to cell proliferation and growth, endometrial remodeling also comprises synthesis and degradation of several molecular components of the extracellular matrix. All of these events are orchestrated by a precise sequence of ovarian hormones and influenced by several types of cytokines. As we have previously reported, an intriguing and rapid increase in collagen fibril diameter occurs in the decidualized areas of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…These results agree with those of another study in rat uterus that shows 30% and 55% clearance of COL I and COL III, respectively, in the implantation site from Day 5.5 to Day 6.5; and 16% and 31% clearance of COL I and COL III, respectively, in the implantation site from Day 6.5 to Day 7.5 [6]. Previous studies in the mouse indicate weaker COL III staining on Day 5 than on later days [7], with reorganization into sparsely distributed, thick intercellular fibrils by Day 7 [39]. The expression pattern of COL IV differs from that of the other three collagen types.…”
Section: Discussionmentioning
confidence: 88%
“…These results agree with those of another study in rat uterus that shows 30% and 55% clearance of COL I and COL III, respectively, in the implantation site from Day 5.5 to Day 6.5; and 16% and 31% clearance of COL I and COL III, respectively, in the implantation site from Day 6.5 to Day 7.5 [6]. Previous studies in the mouse indicate weaker COL III staining on Day 5 than on later days [7], with reorganization into sparsely distributed, thick intercellular fibrils by Day 7 [39]. The expression pattern of COL IV differs from that of the other three collagen types.…”
Section: Discussionmentioning
confidence: 88%
“…We have previously documented that, in mice, remodeling of the extracellular matrix begins early in pregnancy, characterized by synthesis, degradation, and alteration of collagen fibrillogenesis, accompanied by pregnancy‐stage dependent expression of collagen, glycosaminoglycans and proteoglycans. Interestingly, decorin is abolished from the superficial stroma after decidualization and lumican is maintained, although in very low levels (Zorn et al, 1995; San Martin et al, 2003a, b; Spiess and Zorn, 2007). In fact, studies from Vogel and Trotter (1987) showed that decorin and lumican link to fibrilar collagens in vitro , stabilizing thin fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Spiess and Zorn used immunogold localization to show that both thin and thick collagen fibrils present in the pregnant mouse endometrium were formed by type I, III and V collagens. 10 Type V collagen was predominant in the thick collagen fibrils and almost absent in the thin fibrils. 10 Aplin et al also reported that type III and type V collagens and fibronectin were present in endometrial stroma throughout the menstrual cycle as well as in the human first trimester decidua.…”
Section: Discussionmentioning
confidence: 94%
“…10 Type V collagen was predominant in the thick collagen fibrils and almost absent in the thin fibrils. 10 Aplin et al also reported that type III and type V collagens and fibronectin were present in endometrial stroma throughout the menstrual cycle as well as in the human first trimester decidua. 11 Other studies have shown that type V collagen is masked by type I collagen in heteropolymeric fibrils and that type V collagen may regulate the diameter of the major type I collagen fibrils.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation